Unfolding the Unexpectedness of Uncertainty Creative Nonfiction and the Lives of Becoming Teachers - Sinner, Anita; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2013)
Unfolding the Unexpectedness of Uncertainty invites readers to share in the stories of Ruth, Ann and Nathalie as they transition from students to teachers. Rendering their experiences as short stories from the field of teacher education brings a dimension of social biography to scholarship. As creative nonfiction, these stories act as catalysts to understand teacher culture from first-person accounts. Their stories may be described as openings: Ruth$1 (Bs unfolding; Ann$1 (Bs unexpectedness; and Nathalie$1 (Bs uncertainty. Such narratives are exemplars of arts research, extending the purpose, intent, outcomes and dissemination of research by making scholarly study a more intimate and personal experience through the lives of student-teachers. Entering research practices with a perspective that stories are effective teaching tools that represent cultural artefacts, these stories help make sense of practices in public schools and in postsecondary teacher training, and help students, teachers and teacher educators to better understand the operations of the educational system. Unfolding the Unexpectedness of Uncertainty can be used as case studies for undergraduate and graduate students and academic researchers in fields of study involving creative nonfiction and life writing, such as Education, Creative Writing, English, Women$1 (Bs Studies, Social and Cultural Geography, Sociology and Integrated Studies. Social Fictions Series Editorial Advisory Board Carl Bagley, University of Durham, UK Anna Banks, University of Idaho, USA Carolyn Ellis, University of South Florida, USA Rita Irwin, University of British Columbia, Canada J. Gary Knowles, University of Toronto, Canada Laurel Richardson, The Ohio State University (Emeritus), USA Anita Sinner, PhD, is an assistant professor in the Department of Art Education, Faculty of Fine Arts at Concordia University in Montreal, Canada, where she teaches on topics of arts research, curriculum studies, life writing, social and cultural issues in education and interdisciplinary qualitative approaches. Cover art by Ruth, Ann and Nathalie.s
Keywords: Education; Education; Education (general).